Tradition-Based Islamic Education in the Serakalan Haji of the Sasak Community - Muslim, Asbullah; Nasri, Ulyan; Algadri, Wan Syurur Feiruz; Halim, Abdul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to describe the Serakalan Haji as a tradition-based Islamic education mechanism by analyzing how the ritual facilitates the internalization of religious values, the development of social solidarity, and the reproduction of cultural identity in the religious life of the Sasak people in Lombok. Employing a qualitative ethnographic approach, the study draws upon participant observation, in-depth interviews with religious figures and community members, and analysis of ritual documents and oral traditions. The primary data sources consist of direct observation of the ritual, oral narratives from key informants, and local manuscripts and community documents related to Serakalan Haji. The data were analyzed using thematic analysis, which involved coding, categorizing, and interpreting recurring patterns of meaning to understand how the Serakalan ritual functions in transmitting Islamic values, fostering social solidarity, and sustaining cultural identity within the Sasak community. The findings reveal that Serakalan serves as a form of tradition-based Islamic education, grounded in the lived experiences of the community. It nurtures love for the Prophet Muhammad, encourages intergenerational learning, and promotes ethical behavior through emotional and performative engagement. The ritual intensifies during the Hajj season, when acts of pilgrimage and Serakalan reinforce communal bonds, spiritual reciprocity, and collective emotional expression. The elders play a central role in ensuring the continuity of this tradition, functioning as cultural educators and spiritual guides. Ultimately, Serakalan Haji exemplifies how local religious practices can serve as powerful vehicles for Islamic pedagogy, social cohesion, and the embodiment of faith in everyday life.